2003
DOI: 10.1029/2002gl016006
|View full text |Cite
|
Sign up to set email alerts
|

What high altitude observations tell us about the auroral acceleration: A Cluster/DMSP conjunction

Abstract: Magnetic conjugate observations by Cluster and DMSP F14 satellites are used to study the field lines of auroral arc. Cluster is well above the acceleration region and observes upward keV ion beams and bipolar electric structures. The integrated potential at Cluster altitudes shows a dip that is consistent with the keV electron acceleration energy at low altitude. The earthward Poynting flux at Cluster altitudes is comparable to the electron energy flux at low altitudes. Thus, for this event the auroral acceler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 11 publications
8
45
0
Order By: Relevance
“…We see that the density is enhanced in the region of the low potentials. Using magnetic conjunction between the Cluster satellites and DMSP, Vaivads et al [2003] reported that as the Cluster satellites 1, 2 and 3 crossed the auroral arc a density enhancement was found at 4.7R e geocentric altitude while at the low altitude of DMSP (∼800 km) an extended density cavity was found. While the formation of the lowaltitude density cavity is well known from satellites like FAST [McFadden et al, 1999], the density enhancement measurements at high altitude, perhaps in the source region of the auroral arcs, is an unexplained new finding.…”
Section: Potential and Density Structures Of The Moving V-shaped Doubmentioning
confidence: 99%
See 2 more Smart Citations
“…We see that the density is enhanced in the region of the low potentials. Using magnetic conjunction between the Cluster satellites and DMSP, Vaivads et al [2003] reported that as the Cluster satellites 1, 2 and 3 crossed the auroral arc a density enhancement was found at 4.7R e geocentric altitude while at the low altitude of DMSP (∼800 km) an extended density cavity was found. While the formation of the lowaltitude density cavity is well known from satellites like FAST [McFadden et al, 1999], the density enhancement measurements at high altitude, perhaps in the source region of the auroral arcs, is an unexplained new finding.…”
Section: Potential and Density Structures Of The Moving V-shaped Doubmentioning
confidence: 99%
“…We note the density enhancement in the central part of the V-shaped potential structure. Later in section 7 we discuss that the density structure like in Figures 4c and 5b is inferred from observations during magnetic conjunctions between the low-altitude DMSP and high-altitude Cluster satellites [Vaivads et al, 2003].…”
Section: Double Layer and Electron Holes And Their Motionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The association of magnetospheric interfaces with these strong electric fields has been demonstrated in various case studies (e.g. Vaivads et al, 2003;Johansson et al, 2006;Kullen et al, 2008;Liléo et al, 2008). Note that the electrostatic model presented here predicts that transverse ionospheric electric fields can exist on both sides of an arc, which must give rise to oppositely directed plasma convection along the arc (Kullen et al, 2008).…”
Section: Discussionmentioning
confidence: 98%
“…Stronger converging fields lead to higher parallel potential differences, stronger upward field-aligned currents, even higher ionospheric conductivity, and accelerated upgoing ions, all typical of discrete auroral arcs (e.g. Lyons, 1981;Carlson et al, 1998;Vaivads et al, 2003;Figueiredo et al, 2005;Liléo et al, 2008;Echim et al, 2009). A statistical study by Johansson et al (2007) points out that the scale sizes of intense electric field signatures, of the field-aligned currents, and of the density gradients observed above the auroral zone at 5-7 R E geocentric distance were compatible, supporting the overall picture of a magnetospheric interface associated with the arc structure, and determining its thickness.…”
Section: Discussionmentioning
confidence: 99%